2013
DOI: 10.1093/ckj/sft029
|View full text |Cite
|
Sign up to set email alerts
|

Henoch-Schonlein purpura in a renal transplant recipient with prior IgA nephropathy following influenza vaccination

Abstract: Henoch–Schönlein purpura (HSP) is a systemic small-vessel leucocytoclastic vasculitis with deposition of immune complexes containing Immunoglobulin A (IgA). IgA Nephropathy (IgAN) is a glomerulonephritis caused by mesangial deposition of IgA. The onset of HSP, but not IgAN, has been linked to influenza vaccination.We report the first case of HSP with glomerular involvement, in a renal transplant recipient following influenza vaccination. The patient had prior end-stage renal failure (ESRF) secondary to IgAN, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Many, rather old, clinical cases have been published. They describe episodes of one or the other disease within the same siblings, in particular in homozygous twins [ 1 ], simultaneously or successively [ 2 ], in a father and son [ 3 ], in the same patient at two periods of his life [ 4 , 5 , 6 , 7 ] and, more recently, recurrences in kidney allograft in one form or another [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many, rather old, clinical cases have been published. They describe episodes of one or the other disease within the same siblings, in particular in homozygous twins [ 1 ], simultaneously or successively [ 2 ], in a father and son [ 3 ], in the same patient at two periods of his life [ 4 , 5 , 6 , 7 ] and, more recently, recurrences in kidney allograft in one form or another [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…IgA vasculitis flares following vaccinations have been reported previously. 2 Furthermore, it has been reported that patients with IgA nephropathy have a stronger IgA response to intramuscular influenza vaccine than do healthy controls. 3 Moreover, two reports have described three cases of haematuria and IgA nephropathy flares following the second dose of mRNA COVID-19 vaccines in three individuals with biopsy-proven IgA nephropathy, two patients following the mRNA-1273 vaccine, 4 and one after the BNT162b2 (BioNTech-Pfizer) vaccine.…”
mentioning
confidence: 99%
“…The IgAN flare in our patient following the second SARS-CoV-2 vaccine dose without known prior exposure to SARS-CoV-2 suggests it was mediated by a delayed-type hypersensitivity reaction. Vasculitis flare-ups following vaccinations have been reported in the past 2 , 3 .…”
mentioning
confidence: 99%